Immunological characterization of the HIV-tuberculosis associated immune reconstitution inflammatory syndrome - Tadokera, Rabecca (Institute of Infectious Disease and Molecular Medicine, 2015)
While the integration of anti-TB and cART therapies is associated with substantial clinical improvement in the majority of patients, HIV-Tuberculosis associated Immune Reconstitution Inflammatory Syndrome (TB-IRIS) has been shown to occur in a significant subset of these patients. TB-IRIS is an inflammatory complication of the combined treatments for HIV-1 and tuberculosis, which is being reported increasingly, particularly in areas endemic to both diseases. This work aimed to characterise the immunopathogenesis of paradoxical HIV-Tuberculosis associated immune reconstitution inflammatory syndrome.